Reinvigorating Health Systems and Community-Based Services to Improve Maternal Health Outcomes - Sally E. Findley; Henry V. Doctor; Garba M. Ashir; Musa A. Kana; Abu S. Mani; Cathy Green; Godwin Y. Afenyadu (SAGE Publishing, 2015)
Background: Maternal health outcomes in Nigeria, the most populous African nation, are among the worst in the world, and urgent efforts to improve the situation are critical as the deadline (2015) for achieving the Millennium Development Goals draws near. Objective: To evaluate the results of an integrated maternal, newborn, and child health (MNCH) program to improve maternal health outcomes in Northern Nigeria. Design: The intervention model integrated critical health system and community-based improvements aimed at encouraging sustainable MNCH behavior change. Control Local Government Areas received less intense statewide policy changes. Methods: We assessed the impact of the intervention on maternal health outcomes in 3 northern Nigerian states by comparing data from 2360 women in 2009 and 4628 women in 2013 who had a birth or pregnancy in the 5 years prior to the survey. Results: From 2009 to 2013, women with standing permission from their husband to go to the health center doubled (from 40.2% to 82.7%), and health care utilization increased. The proportions of women who delivered with a skilled birth attendant increased from 11.2% to 23.9%, and the proportion of women having at least 1 antenatal care (ANC) visit doubled from 24.9% to 48.8%. ANC was increasingly provided by trained community health extension workers at the primary health center, who provided ANC to 34% of all women with recent pregnancies in 2013. In 2013, 22% of women knew at least 4 maternal danger signs compared with 10% in 2009. Improvements were significantly greater in the intervention communities that received the additional demand-side interventions. Conclusions: The improvements between 2009 and 2013 demonstrate the measurable impact on maternal health outcomes of the program through local communities and primary health care services. The significant improvements in communities with the complete intervention show the importance of an integrated approach blending supply- and demand-side interventions.